Antibiotic-contaminated wastewater irrigated vegetables pose resistance selection risks to the gut microbiome. (September 2020) - Gudda, Fredrick Owino; Waigi, Michael Gatheru; Odinga, Emmanuel Stephen; Yang, Bing; Carter, Laura; Gao, Yanzheng
Abstract: Wastewater reuse in food crop irrigation has led to agroecosystem pollution concerns and human health risks. However, there is limited attention on the relationship of sub-lethal antibiotic levels in vegetables and resistance selection. Most risk assessment studies show non-significant toxicity, but overlook the link between antibiotics in crops and propagation of gut microbiome resistance selection. The review highlights the risk of antibiotics in treated water used for irrigation, uptake, and accumulation in edible vegetable parts. Moreover, it elucidates the risks to the adaptive resistance selection of the gut microbiome from sub-lethal antibiotic levels, as a result of dietary contaminated vegetables. Experiments have reported that bacterial resistance selection is possible at concentrations that are several hundred-folds lower than lethal effect levels on susceptible cells. Consequently, mutants selected at low antibiotic levels, such as those from vegetables, are fitter and more resistant compared to those selected at high concentrations. Necessary standardization, such as the development of minimum acceptable antibiotic limits allowable in food crop irrigation water, with a focus on minimum selection concentration, and not only toxicity, has been proposed. Wastewater irrigation offers environmental benefits and can contribute to food security, but it has non-addressed risks. Research gaps, future perspectives, and frameworks of mitigating the potential risks are discussed. Graphical abstract: Image 1 Highlights: Wastewater irrigation continuously expose crops to contaminants such as antibiotics. Antibiotics in irrigated wastewater can accumulate in edibles parts of vegetables. Sub-lethal antibiotic levels can induce adaptive resistance in the gut microbiome. Resistance selection from vegetables are mostly unexplored, despite the risks. Research gaps, future perspectives, and mitigation frameworks are proposed. Abstract : Risk assessment of antibiotics accumulated in vegetables should be based on toxicity and minimum resistance selection concentrations of the gut microbiome.